When Religious Folk Practice Meet Karl Marx: Courts’ Response to Ghost Marriage in Modern China - Zhou, Wenzhang (Religions, 2023)
As religious folk practice is regarded as a radical departure from Marxist atheism, the abnormal existence of ghost marriages under the Chinese socialist regime has attracted wide scholarly attention in anthropology and sociology. However, few scholars have focused on how Chinese courts treat religious folk practices, such as ghost marriages, despite the official socialist ideology. Based on the typological analysis and case study involving 260 ghost marriage cases, the authors argue about the judicial activism of Chinese courts towards atheist ideology in religious folk practices. The findings of this study are twofold. First, the Chinese courts’ attitudes toward ghost marriage cases are pluralistic, reflecting the Chinese legal system’s selective obedience to the socialist ideology. Through the application of different legal interpretations of relevant laws, Chinese courts have shown three attitudes towards ghost marriages: encouragement, tolerance, and suppression. The first two attitudes can be regarded as supportive supervision of religious folk practice. Three factors tended to affect the courts’ attitudes towards ghost marriages: courts’ hierarchical level, parties’ claims, and whether ghost marriage rituals are performed. Second, further analysis suggests that RPC’s guerrilla-style governance strategy in the Chinese legal system allows it to deal with ghost marriage with more flexibility, even overriding its fundamentalist ideology. The guerrilla-style tactic is often used by the Chinese courts to handle matters of religious folk practices in a pluralistic manner. Overall, the courts’ pluralistic attitudes towards ghost marriage is that of modest tolerance and cooperation of religious folk practices based on the RPC’s model of governance.